Spinal myoclonus - Hopkins, A. P. (1974)
A case of rhythmic myoclonus affecting only the lower part of the body is described. This occurred as an acute self-limiting illness. The changes in the cerebrospinal fluid (CSF) suggested a viral infection. Clinical and electrophysiological findings indicated that the involuntary movements were arising at spinal level and were independent of suprasegmental influences. There are few previously reported cases of spinal myoclonus, all different in various respects from the present one, which is reminiscent of the results of experimental inoculation of virus into feline spinal cord.